Change management for organizations : lessons from political upheaval in India - Sadangi, Chandan Kumar; Mohapatra, Sanjay (Emerald Publishing Limited, 2017)
Change management is a better or smarter approach to initiate a change via behavioral aspects. As it is the power to innovate which is a unique strength for companies, the need for strategies to tackle change management within the firm is evident. This work demonstrates how a firm can learn change management from political upheavals, thus providing benefits to the entire value chain. Through examples and case studies from such unrest throughout India's diverse history, Mohapatra and Sadangi combine their academic and industry experience to show the need for business alignment with change management strategy.